2015
DOI: 10.1108/ijph-05-2014-0012
|View full text |Cite
|
Sign up to set email alerts
|

Incarcerated women's HPV awareness, beliefs, and experiences

Abstract: Purpose The purpose of this paper is to explore incarcerated women’s awareness, beliefs, and experiences with human papillomavirus (HPV) infection and vaccination. Design/methodology/approach Researchers conducted focus groups with 45 incarcerated women in an urban Midwestern US jail to assess how women talked about their Papanicolaou (Pap) test screening and abnormal Pap test follow-up experiences. Some focus group questions specifically assessed individual awareness, beliefs, and experiences with HPV infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…It has been reported that imprisoned women are at increased risk of cervical cancer but are also less likely to have been screened for cervical cancer [ 7 ]. These women report multiple risk factors for HPV and cervical cancer, and have up to a fivefold increased risk of cervical cancer when compared with women who are not incarcerated [ 8 ]. As at September 2019, it was estimated that Ghana had a prison population rate of close to 50 per 100,000 population, with females comprising 1.2% of this number, a total of 15,463 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that imprisoned women are at increased risk of cervical cancer but are also less likely to have been screened for cervical cancer [ 7 ]. These women report multiple risk factors for HPV and cervical cancer, and have up to a fivefold increased risk of cervical cancer when compared with women who are not incarcerated [ 8 ]. As at September 2019, it was estimated that Ghana had a prison population rate of close to 50 per 100,000 population, with females comprising 1.2% of this number, a total of 15,463 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Awareness and knowledge of HPV and the vaccine has trended up in the general population (Blake et al, 2015; Gerend & Magloire, 2008; Sherman et al, 2016) but has lagged in underserved populations, which tend to have significant demographic overlap with incarcerated populations (Galbraith et al, 2016; Pankey & Ramaswamy, 2015; Strohl et al, 2015; Watkins, Reitzel, Wetter, & McNeill, 2015). Although infection and vaccine awareness in this sample was higher than in a prior study of incarcerated women (Pankey & Ramaswamy, 2015), vaccine awareness was lower than in the general population, where it has ranged from around 60% to nearly 90% in recent years (Beshers, Murphy, Fix, & Mahoney, 2015; Blake et al, 2015; Bond et al, 2016; Glenn et al, 2015). Awareness of the vaccine was also far lower in this population than awareness of the virus itself, which mirrors findings in the general population (Garcini et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies of HPV attitudes and vaccine acceptability have been conducted in the general population, but few have focused on incarcerated populations. One qualitative study of incarcerated women with histories of abnormal Pap tests suggested limited awareness of and knowledge gaps about HPV and the vaccine (Pankey & Ramaswamy, 2015). Other studies of prison populations have shown that incarcerated individuals would be amenable to in-prison vaccination against infectious diseases such as hepatitis B and HIV (Lally et al, 2006; Vallabhaneni et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies show that there can be marked differences in service provision between prisons with discontinuity of health services being common. This led to the need to establish a consensus policy between prisons and health services supported by national directives guaranteeing necessary actions and measures to make the screening, control, and treatment of cervical cancer viable among imprisoned women [ 3 , 15 , 16 ]. Therefore, in 2014 a joint decision was reached between health and justice institutions in Brazil, which required municipalities to be responsible for healthcare provision in prisons [ 17 ].…”
Section: Introductionmentioning
confidence: 99%